Synthesis and Characterization of Tin(IV) Complexes with O-and N-Donor Ligands - Mallikarjuna, N.N.; Angadi, S.D.; Kulkarni, V.H. (Asian Journal of Chemistry, 2010)
The Schiff bases have been prepared by reacting ninhydrin and various substituted amines. The Sn(IV) complexes have been prepared by reacting tin tetrachloride with these Schiff bases in an alcoholic medium. All these complexes are violet to brown in colour and amorphous in nature. The complexes are non-electrolytes in DMF. Elemental analysis confirms the stoichiometry of the type L2SnCI4. The IR spectral observation favours the coordination of C=O to the Sn(IV) ion through oxygen. Sn(IV) exhibits coordination number of six in these complexes.